Platelet parameters and risk of hypertension disorders of pregnancy: a propensity score adjusted analysis. (19th May 2022) - Lin, Shanshan; Zhang, Lifang; Shen, Songying; Wei, Dongmei; Lu, Jinhua; Chen, Xiaojuan; Chen, Qiaozhu; Xia, Xiaoyan; Xiu, Qiu
Abstract: While the role of platelets in cardiovascular diseases among the general population has been widely reported, evidence is inconsistent regarding the association between platelet indices with hypertension in pregnant women. In this study, we explored the associations between platelet parameters before 20 gestational weeks, an understudied period, with hypertensive disorders of pregnancy (HDP), including preeclampsia/eclampsia (PEEC) and gestational hypertension (GH). Based on the Born in Guangzhou Cohort Study, 12053 singleton pregnant women with platelet parameters, including platelet count (PC), mean platelet volume (MPV), plateletcrit (PCT), and platelet distribution width (PDW) measured at 14–19 gestational weeks were included. Conventional multivariable adjustment and propensity score analysis were used to control for confounders. The restricted cubic spline showed that the risk of PEEC increased linearly for PC, and non-linearly for PCT. For GH, the risk increased linearly for PC, MPV, and PCT, and non-linearly for PDW. When these indices were categorized into quintiles, women with higher PC and PCT were associated with increased risk of both PEEC and GH. Women with MPV exceeding the second quintile (≥ 8.8 fL) had a greater risk for GH, but not for PEEC. When HDP was classified into two groups (early- vs late-onset) based on the occurrence time, significant associations persisted for early-onset PEEC, early-onset GH, and late-onset GH. In conclusion, increased PC and PCT before 20 weeks of gestation were both associated with higher risk of PEEC and GH, while elevated MPV was only linked to GH.